2010
DOI: 10.1111/j.1365-2516.2009.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Haemophilia Joint Health Score in study of episodically treated boys with severe haemophilia A and B in Lithuania

Abstract: Musculoskeletal outcome remains the major hallmark of haemophilia. The purpose of the study was to assess joint status using a new musculoskeletal assessment tool in children with haemophilia and describe the development of haemophilic arthropathy during childhood and puberty focussing on the age of remarkable changes. The prospective study involved Lithuanian patients aged 4-17 years with severe haemophilia A and B, no signs of inhibitors and treatment on-demand. Patients were subdivided into two groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
4
27
0
2
Order By: Relevance
“…In patients on the most intensive regimen (‘full’ regimen), joint changes measured by HJHS only appeared after the age of 13 years . In patients treated on demand, HJHS was already increased before the age of 10 years, and afterwards significant worsening of HJHS was observed . It therefore seems likely that larger differences between treatment groups, such as when comparing prophylaxis and on demand treatment , would have been picked up despite inter‐observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…In patients on the most intensive regimen (‘full’ regimen), joint changes measured by HJHS only appeared after the age of 13 years . In patients treated on demand, HJHS was already increased before the age of 10 years, and afterwards significant worsening of HJHS was observed . It therefore seems likely that larger differences between treatment groups, such as when comparing prophylaxis and on demand treatment , would have been picked up despite inter‐observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…It is still widely used (16) because it is easy to perform and capable of providing an extensive musculoskeletal assessment (4) . A tape measure and a goniometer are used in the examination of the knees, ankles, elbows, and hips for the presence of edema, atrophy, crepitus, flexion contractures, axial deformities, loss of range of motion and instability; points are assigned to each finding, according to severity and are summed.…”
Section: Methodsmentioning
confidence: 99%
“…However, earlier studies showed that this measurement also applicable for episodically treated patients. 15,16 Study in Lithuania 16 reported HJHS in 20 hemophilia children receiving episodic treatment, mean total scores in patients aged 4-9 years was significantly lower compare to older children aged 10-17 years (11.6 vs 31.5, respectively). Study in Pakistan 15 on severe (n=59) and non-severe (n=29) hemophilic patients receiving episodic treatment divided into three developmental age groups (<12 years, 12-16 years, and >16 years), the HJHS and Gilbert scores were significantly lower in the youngest group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%